FRUITFUL METHODS IN THE INSTRUCTING OF THE SECOND LANGUAGE - Mavlanova Mohira Umrbek qizi (Journal of Higher Education and Academic Advancement, 2024)
We all know that the demand for learning a foreign language is increasing every year. This increases the need for modern methods of foreign language teaching in today's competitive process. This article talks about interactive methods of teaching a foreign language.